Peningkatan Kinerja Badan Usaha Milik Desa (BUMDesa) Pala Opat Melalui Orientasi Kewirausaan - Fina, Yohanes; Hermenegildus K. Talan; Alfrido Naiheli (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to explain the improvement of the Performance of Village-Owned Enterprises (BUMDes) Pala Opat through Entrepreneurial Orientation in Tubu Village, Bikomi Nilulat District, North Central Timor Regency. The research method used is a qualitative research method. The research location is Tubu Village, Bikomi Nilulat District, North Central Timor Regency. The results of the study indicate that entrepreneurial orientation has a significant impact on BUMDesa Performance. A good entrepreneurial orientation will improve Performance. It can be concluded that thus, one way to maintain and improve BUMDesa Performance to the maximum is through entrepreneurial orientation in the form of an innovative, proactive and risk-taking attitude. Keywords: BUMDesa Performance, Entrepreneurial Orientation.